Prosthesis-sparing aortic root replacement following aortic valve replacement. (July 2014) - Takano, Tamaki; Wada, Yuko; Seto, Tatsuichiro; Terasaki, Takamitsu; Fukui, Daisuke; Amano, Jun
Reoperation on the aortic root is considered to be challenging because of high hospital mortality. Prosthesis-sparing aortic root replacement, in which the aortic prosthesis is preserved during reoperation, and could avoid passing sutures through the weakened aortic annuls after the initial prosthesis has been removed. We report 3 cases of prosthesis-sparing aortic root replacement. Prior procedures were aortic valve replacement and the Bentall operation 14 to 35 years previously. Postoperative courses were uneventful, with no signs of pseudoaneurysm or valve malfunction observed during follow-up periods of 93 to 360 days.